Sejarah Peradaban Islam - Siti Halimang (Al-'Adl, 2009)
Jurisdiction is one of the Institution in fulfilling intention live society in straightening of justice and law, has been recognized by before Islam. Nation Arab before Islam have owned qadi to finish all their dispute, but they not yet owned code/law written able to be made by hold all qadi. They verdict among them by corresponding to hereditary them habit, and from opinion of tribe heads or from their people who of wise approach is known as his opinion exact people who, and confiscate rights with marking and hunch, intelligence of their jurist is caused them more prioritize to decide law with marking and priest from at by means of…other evidence, like confession or eyewitness.            In study jurisdiction of Islam in Indonesia and jurisdiction in general, recognized by various special term or word which become device from a concept, among others religion court, the jurisdiction of Islam, the jurisdiction of Islam, justice of religion and so on. But to avoid by mistake of[is understanding of, if which meant “jurisdiction of Islam in Indonesia”, is “religion court” besides there are also other term related to that terms, both for having a meaning of-of a kind and related to him and become explain of position from each; every that term. That terms can know them by the meaning of in so many sources that are in dictionary, law and regulation and encyclopedia. All that term or words is told in different understanding. Is sometimes told also in is same understanding. That thing is to have jetty to form two more term of the public, that is justice and jurisdiction.